Health, Financial Incentives and Retirement in Spain - Esen Erdogan-Ciftci; Eddy Van Doorslaer; Angel Lopez-Nicolas (Tinbergen Institute, 2008)
We estimate the impact of health and financial incentives on the retirement transitions of older workers in Spain. Individual measures of pension wealth, peak and accrual values are constructed using labor market histories and health shocks are derived as changes in a composite health stock measure over time. We examine labour market exits into both old age retirement and a broader definition of retirement including inactivity, while controlling for unobserved heterogeneity. We find that pension wealth, accrual and peak value are significant determinants of retirement decisions, although their effect is weaker in the case of the broad definition of retirement. Initial health stock shows a significant impact on both definitions of retirement. Only large negative health shocks have a significant effect on the probability of entering the broader definition of retirement. Unlike previous literature, we find that (i) financial incentives, when measured adequately, exert a greater impact on retirement behaviour than health shocks, and (ii) initial health stock plays a more important role than health shocks in determining retirement decisions. We also perform simulations of a recently enacted reform of pension incentives and show how its expected effects compare to those of health improvements.
Keywords: H55; I10; J26; 330; Health; Retirement; Social security and public pensions; Ältere Arbeitskräfte; Altersgrenze; Entscheidung bei Unsicherheit; Gesundheit; Schock; Vergleich; Ökonomischer Anreiz; Gesetzliche Rentenversicherung; Spanien